PENGEMBANGAN BAHAN AJAR MENULIS NARASI BERBASIS MEDIA BAGAN POHON DI KELAS V SEKOLAH DASAR - Nurjani Nurjani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2018)
The purpose of this study was to develop tree chart media used to teach writing narration at the fifth grade of elementary school level. The research design was Research and Development with ADDIE model. The subjects of the research were the students and teacher at the fifth class of SDI Al-Azhar Muhammadiyah Simabur. The research instruments were 1) the expert and practitioner validity assessment sheets, 2) practicality instruments such as, lesson plans, questionnaire of teacher and student response of practicality, and validity assessment sheets, and 3) effectivity instrument namely students’ writing test result. The data were analyzed descriptively. The result shows that the developed teaching materials were extremely valid indicated by both expert validity gain 92% and practitioner validity gain 93%. In terms of practicality, the teaching materials were very practical indicated by both teacher response 93.3% and the student response 92.9%. At last, the effectivity was shown by the students activity while doing writing. In summary, the tree chart-based-teaching media in teaching writing narration is valid, practical, and effective to the fifith grade students.